2017
DOI: 10.3389/fpls.2017.01743
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Traits and Molecular Marker Identification of Wheat–Aegilops caudata Addition Lines

Abstract: Aegilops caudata is an important gene source for wheat breeding. Intensive evaluation of its utilization value is an essential first step prior to its application in breeding. In this research, the agronomical and quality traits of Triticum aestivum-Ae. caudata additions B–G (homoeologous groups not identified) were analyzed and evaluated. Disease resistance tests showed that chromosome D of Ae. caudata might possess leaf rust resistance, and chromosome E might carry stem rust and powdery mildew resistance gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…caudata in a wheat background. More recently, Gong et al (2017) developed EST-based markers and Niu et al (2018) developed SSR markers for the detection of Ae. caudata chromatin in a wheat background.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…caudata in a wheat background. More recently, Gong et al (2017) developed EST-based markers and Niu et al (2018) developed SSR markers for the detection of Ae. caudata chromatin in a wheat background.…”
Section: Discussionmentioning
confidence: 99%
“…The variation observed in the results indicates the presence of genomic rearrangements. Recently, studies by Danilova et al (2017), Gong et al (2017) and Niu et al (2018) on the Alcedo- Ae. caudata additions lines found that the C-genome chromosomes carried several inversions and translocations but did not agree on the rearrangements carried by each chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations